Peripartum Cardiomyopathy and Systemic Lupus Erythematosus Carditis, a diagnostic dilemma - Poudel, Binod; Karki, Prashanna; Lamsal, Aastha; Poudel, Chandra Mani (Nepalese Heart Journal, 2020)
A young woman at 8 months postpartum presented with dyspnoea, orthopnoea and swelling of lower limbs in which physical examination, chest radiography and echocardiogram were suggestive of acute congestive heart failure with left ventricle dilatation and dysfunction. A suspicion of peripartum cardiomyopathy was made and treated with conventional drug therapy but the patient continued to develop multiple episodes of heart failure. Over time she developed fever and polyarthritis following which autoantibodies, complement level and 24-hour urinary protein were done which helped us to make the diagnosis of Systemic Lupus Erythematosus (SLE) nephritis. The patient was started on high dose corticosteroids. However, after a week, patient developed cardiogenic shock following which intravenous pulse Cyclophosphamide was started and the patient improved clinically and biochemically.